Normative Review of Legal Protection for Athletes with Achievements in Lampung Province - Siagian, Debora Shintiya; Simarmata, Ocniel Juandi; Alfian, Angga (CV. Rayyan Dwi Bharata, 2024)
The phenomenon of sports in Indonesia, since the time of the kings before colonization until now, is very important to be studied for the development of sports in the current context and future context. The sport of hunting for example, which later developed into archery is a tangible result of the development of the sport. Nowadays when we hear the word